Addition of Herbal Supplements in Feed on the Growth and Survival Rate of Cachama (Colossoma macropomum) with the Recirculation System - Wishal Novan Pradana; Mulyadi Mulyadi; Iskandar Putra (Faculty of Fisheries and Marine, Universitas Riau, 2022)
This study aims to determine the best dose of herbal supplements in feed for growth and survival of Colossoma macropomum with a recirculation system. This research was conducted from 27 November - 6 January 2021 at the UPT Experiment Pool Faculty of Fisheries and Marine, University of Riau. The container used was a black tub with a volume of 100 L as many as 15 units with a stocking density of 20 individuals / 60 L. This study used a one-factor completely randomized design (CRD) method with five levels of treatment and three replications. The level of treatment applied in this study was P0 = without giving herbal supplements (control), P1 = doses of herbal supplements 100 mL / kg of feed, P2 = 200 mL/kg of feed, P3 = 300 mL / kg of feed, and P4 = 400 mL / kg of feed. The results showed that giving herbal supplements to feed with different doses had a significant effect (P <0.05) on growth but had no significant effect (P> 0.05) on the survival of Colossoma macropomum. The best treatment was found at the herbal supplement dosage of 300 ml / kg of feed, which resulted in absolute weight growth (24.24 g), absolute length growth (5.04 cm), specific growth rate (5.29%), feed efficiency (137, 96%), feed conversion ratio (0.72), survival rate (93.3%), total erythrocytes 1.64x104 cells / mm3, hemoglobin level 9.00 g/dL and blood glucose 89.33 mg/dL.